Guided Tissue Regeneration Membranes: Review of Innovations and Applications in Immunocompromised Patients - Man Hung; Katherine Sanders; Aditya Deshpande; Roshni Trivedi; Connor Schwartz; Amir Mohajeri (Applied Sciences)
Guided tissue regeneration (GTR) membranes are pivotal in regenerative medicine. While their effectiveness is established in general populations, their application in immunocompromised patients, such as those with diabetes or cancer, remains underexplored. This review evaluated evidence on GTR membranes in immunocompromised settings, focusing on their mechanisms, outcomes, and challenges posed by systemic conditions. A systematic search identified studies on GTR use in these populations. Inclusion criteria were peer-reviewed articles in English on human samples or relevant preclinical models. Of 218 articles, 5 met the criteria. These highlighted advancements in GTR technologies, such as stem cell integration, growth factor-enriched scaffolds, and scaffold-free tissue engineering. Stem cell-based approaches improved regeneration, especially with biomimetic designs incorporating bone morphogenetic protein-2. Innovations like microcavity-rich scaffolds enhanced angiogenesis and osteogenesis, while scaffold-free constructs minimized immunogenicity and supported functional tissue regeneration. Preclinical models demonstrated GTR membranes’ potential for addressing large-scale tissue deficits in compromised environments. GTR membranes show promise for immunocompromised patients, but further research is needed to validate their clinical efficacy, address patient-specific challenges, and evaluate long-term outcomes. These technologies could transform regenerative medicine, providing sustainable solutions for high-risk populations.